2007
DOI: 10.1007/s11259-007-3475-9
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Osteological Development of the Hyoid Bone in the New Zealand White Rabbit

Abstract: This study augments knowledge of bone growth by observing the development of the hyoid bone in the New Zealand White rabbit. Preserved hyoid bones representing five different age periods, each period including five individuals and the total number of animals being 25, were fixed in 3.5% formaldehyde solution and 95% ethanol, followed by a pure acetone bath. They were then stained with an alcian blue-alizarin red combination. The mode of bone formation was intracartilaginous type ossification. While the basihyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This result revealed that the hyoid bone in the ostrich was different from some birds and completely different from the mammals (Koebke, 1978 andAtalgin et al, 2007). The basic components of the ostrichhyoid boneweretwo parts; basihyoid and horns.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This result revealed that the hyoid bone in the ostrich was different from some birds and completely different from the mammals (Koebke, 1978 andAtalgin et al, 2007). The basic components of the ostrichhyoid boneweretwo parts; basihyoid and horns.…”
Section: Discussionmentioning
confidence: 89%
“…Available literature about the ostrichare still very little andmysterious. The anatomy of the hyoid bone was previously studied in most mammals (Hilloowala, 1975;Koebke, 1978 andAtalgin, Kürtül, Bozkurt, 2007;Röck, 2009 andBudras et al2011) The structure of the hyobranchial apparatus of the ostrich has received wider attention (Bonga Tomlinson 2000;Porcescu 2007;Jackowiak and Ludwig 2008;Tadjalli et al, 2008;Guimarães et al,2009;Crole and Soley 2112b).In birds, the hyoid apparatus varies in size, shape and the number of bones (Johnston2014). The positions of the hyoid bone and the larynx can be clearly depicted and the upper part of the hyoid bone also connects to the cranium( Hideto 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques including single and double staining techniques, radiography, ultrasonography, MR, and various histological staining methods are being performed to visualize ossification stages. Particularly, double staining techniques have been successfully used in experimental studies of the bone development of fishes, birds, mice, rabbits and reptiles 3,7,8 . On the other hand, studies performed on the bone development of the pig, which has been recently used increasingly as an experimental model, seem to be limited.…”
Section: Introductionmentioning
confidence: 99%
“…It is attached to the styloid process of the petrous part of the temporal bone by a rod of cartilage, the tympanohyoid (Hillmann, 1975). The anatomy and development of the hyoid bone was previously studied in most mammals (Hilloowala, 1975, Koebke, 1978and Atalgin et al, 2007; however, in the camel it is still obscure. Therefore, the aim of this study is to follow the development of the hyoid bone in the one humped camel (Camelus dromedarius) from the anatomical and embryological point of view.…”
Section: Introductionmentioning
confidence: 99%